Problems Implementing the Independent Curriculum in History Learning at SMA Negeri 1 Sarudu - Ratna; Rore, Idrus; Nugroho, Fajar; Iskandar (Kirana Publisher (KNPub), 2025)
Challenges in Implementing the Merdeka Curriculum in History Learning at SMA Negeri 1 Sarudu. Skripsi. Bachelor’s degree. History Education Study Program, Social Science Education Department, Teacher Training, and Education Faculty, Tadulako University. Under the supervision of Fajar Nugroho. This research aims to describe the implementation process, identify the challenges encountered, and examine the solutions applied in applying the Merdeka Curriculum in history learning at SMA Negeri 1 Sarudu. This research used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes stages of data reduction, data presentation, and conclusion. The research results show that implementing the Merdeka Curriculum at SMA Negeri 1 Sarudu encompasses three stages: planning, implementation, and evaluation, centred on students' needs and characteristics. In the process, various problems were found, including student objections to P5 projects, teachers' difficulties in implementing differentiated learning, facility limitations, teachers' lack of initial understanding, and constraints in assessment time management. The solutions implemented by the school and teachers include socialising the benefits of P5, student mentoring, learning style mapping, teacher training, facility optimisation, and more structured assessment scheduling. This research concludes that implementing the Merdeka Curriculum at SMA Negeri 1 Sarudu still faces challenges, but these can be overcome through collaboration between the school and teachers so that history learning runs more effectively and in line with the principles of independent learning.